Pemanfaatan Augmented Reality Untuk Media Pembelajaran Alat Transportasi Bagi Anak Tunagrahita Sedang - Dimas Dwi Kurniawan; Donny Avianto (Journal of Information System Research (JOSH), 2023)
A comparison between conventional teaching methods and modern technology reveals a significant difference in the effectiveness and efficiency of educating moderately mentally handicapped children or D3 C class. The available learning materials lack innovation. Monotonous material design that doesn't support interactivity can reduce the interest and engagement of mentally handicapped children. Therefore, the development of more engaging materials that meet their needs is required. D3 C class students with intellectual disabilities require special attention in the use of educational media, considering the current learning materials tend to be monotonous and lacking innovation. Therefore, Augmented Reality (AR)-based learning media can be a promising solution to enhance the quality of learning about various modes of transportation. Interactive AR-based applications enable the introduction of various modes of transportation in a more engaging and interactive way, involving visual and auditory aspects in learning. In application testing, it was proven that the speed of displaying 3D objects was very fast, taking only 2.3 seconds. This contributes to smooth and effective learning for D3 C class mentally handicapped children. Surveys conducted with teachers who have used this AR application indicate a tendency towards positive responses, with the majority of teachers responding "Agree" or "Strongly Agree" to the 10 statements provided. The use of AR in the MDLC approach offers significant potential for improving the education of D3 C class mentally handicapped children. Positive responses to AR reflect innovation in this learning approach, which focuses on individual development, integrated support, and inclusive education. However, it is important to always emphasize supervision to ensure effective AR use, so that children can benefit from a more engaging and tailored learning experience. Thus, the use of AR in the education of D3 C class mentally handicapped children has significant potential to provide innovative and effective learning in various modes of transportation, thereby helping them in their educational process. This research creates a learning method for studying means of transportation for moderately mentally handicapped children using AR technology, which provides innovation in modern times.